The implementation of Integrated Management Systems (IMS) in construction organizations in Malaysia - Ramli, Nor Fazira; Haron, Nuzul Azam; Ales@Alias, Aidi Hizami; Harun, Aizul Nahar (Penerbit UTM Press, 2023)
An Integrated Management System (IMS) combines different management systems into one complete system. This paper aims to determine the intention and effectiveness of the IMS being implemented in construction organizations in Malaysia. The problem statement in this study is the number of documents in IMS still needs to be more prominent since the adoption of the standard still needs to be improved. This study aims to give awareness to the company so that they understand their intention to implement the IMS and the effect that will get on the implementation process. This study also will provide a framework that will be a guideline for the company to start with the implementation process and be certified as an IMS company. This study used quantitative and qualitative study methods. The study takes place on the construction company in Klang Valley that implemented the IMS. The survey has been done for the quantitative study to check on the understanding of the company for the intention and effectiveness of the IMS implementation. Meanwhile, for the qualitative study, the semi-structured interview session was done with five subject matter experts (SMEs) in the IMS implantation. The interview validates the research process and the framework's effectiveness. As a result, the study helps the companies to clearly understand their intention to implement the IMS and the effectiveness of IMS in their companies. The framework design also will help the company to have proper guidelines starting from the implementation until the continuous improvement after certification by the certification body.